37 Early pregnancy detection in cattle by analysis of maternal circulating microRNA expression. (28th November 2020) - DeCarlo, Andrea N; Parrish, Joseph; Long, Nathan; Pratt, Scott
Abstract: Pregnancy detection in cattle is performed by rectal palpation, transrectal ultrasonography or detection of pregnancy associated glycoproteins at approximately d 28 of gestation. Majority of embryonic loss in cattle occurs much earlier. MicroRNAs (miRNAs) are excellent markers for physiological states including pregnancy. The objective of this experiment was to assess expression of miRNAs in maternal serum to serve as markers for pregnancy detection at d 18 post-artificial insemination. Cows of varying age and parity (n = 80) were synchronized using a 7-d Co Synch and CIDR estrous synchronization protocol. One insemination by a single sire was performed 60 to 66 h following CIDR removal. Blood was collected via jugular venipuncture on d 0 and 18 post-insemination. Total RNA isolation was performed using PAXgene Blood RNA kit (PreAnalytiX, Hombrechtikon, Switzerland) or by miRNeasy (Qiagen, Hilden, Germany). Ultrasound was performed d 30 of gestation. Taqman microRNA assay utilizing primers for Let7a, mir-16, 15b, 25, and 26 was performed on RNA from whole blood and serum in pregnant (n = 10) and open (n = 10) cows. Analysis of variance and pair-wise student's t-test among LSMeans for relative abundance were performed with fixed effects for pregnancy, day, isolation, and their interactions. MicroRNA abundance did not differ due to pregnancy. Relative abundance for miR-16 increased in d 18 (1.86 ± 0.49) compared to d 0 samples (3.42 ± 0.48), regardless of pregnancy status or isolation method (P = 0.03). Let-7a (serum, 0.99 ± 0.98; PAXgene, 6.25 ± 0.87), miR-15b (serum, 0.59 ± 1.67; PAXgene, 12.44 ± 1.48) and miR-26 (serum, 1.44 ± 1.2; PAXgene, 7.64 ± 1.06) relative abundance was higher in serum compared to PAXgene isolated samples (P < 0.05). These results disagree with previous reports and indicate that these candidate miRNAs are not a reliable indicator for early pregnancy detection in cattle.